Efficient Degradation of TCE in Groundwater Using Pd and Electro-generated H(2) and O(2): A Shift in Pathway from Hydrodechlorination to Oxidation in the Presence of Ferrous Ions - Yuan, Songhu (2012)
Degradation of trichloroethylene (TCE) in simulated groundwater by Pd and electro-generated H(2) and O(2) is investigated in the absence and presence of Fe(II). In the absence of Fe(II), hydrodechlorination dominates TCE degradation, with accumulation of H(2)O(2) up to 17 mg/L. Under weak acidity, low concentrations of oxidizing •OH radical are detected due to decomposition of H(2)O(2), slightly contributing to TCE degradation via oxidation. In the presence of Fe(II), the degradation efficiency of TCE at 396 μM improves to 94.9% within 80 min. The product distribution proves that the degradation pathway shifts from 79% hydrodechlorination in the absence of Fe(II) to 84% •OH oxidation in the presence of Fe(II). TCE degradation follows zeroth-order kinetics with rate constants increasing from 2.0 to 4.6 μM/min with increasing initial Fe(II) concentration from 0 to 27.3 mg/L at pH 4. A good correlation between TCE degradation rate constants and •OH generation rate constants confirms that •OH is the predominant reactive species for TCE oxidation. Presence of 10 mM Na(2)SO(4), NaCl, NaNO(3), NaHCO(3), K(2)SO(4), CaSO(4) and MgSO(4) does not significantly influence degradation, but sulfite and sulfide greatly enhance and slightly suppresses degradation, respectively. A novel Pd-based electrochemical process is proposed for groundwater remediation.